Can we justify EU Cohesion Policy? - Roman Römisch (The Vienna Institute for International Economic Studies (wiiw), 2020)
This paper asks whether we can, from an economic point of view, justify the EU Cohesion Policy. To this end, our research - using structural equation modelling, macro-economic modelling and regional inputoutput analysis - found a) positive dynamic effects of Cohesion Policy on regional growth, b) small static effects on output if parts of the Cohesion Policy funds are reallocated to the strongest EU economies and c) strong demand spillovers from the less-developed to the more-developed regions. For us, the dynamic Cohesion Policy gains in growth outweigh the static allocation inefficiency. Additionally, the spillovers from the less-developed regions mitigate potential losses in the more-developed regions. Therefore, our answer to the question 'Can we justify EU Cohesion Policy from an economic point of view?' is 'Yes, we can.'
Keywords: R11; R58; 330; Cohesion Policy; EU regions; regional development